2011
DOI: 10.3109/09513590.2011.593669
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of adenomyosis in women operated for benign gynecological diseases

Abstract: AG is an enigmatic disease frequently causing gynecologic complaints and endomyometrial junction deterioration during endometrial sampling may be a trigger point for developing AG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…[83][84][85] The results for menorrhagia and dysmenorrhea have been less consistent when adenomyosis, or adenomyosis with leiomyomas, has been compared with those with pathology-confirmed leiomyomas. 12,43,[86][87][88][89][90][91][92][93] Although in several of these studies, patients with adenomyosis with or without leiomyomas appear to experience a greater frequency of dysmenorrhea than patients with leiomyomas. 12,86,87,90,92 One frequently cited study has suggested that adenomyosis is an incidental finding and not a source of symptoms.…”
Section: Symptomatologymentioning
confidence: 99%
“…[83][84][85] The results for menorrhagia and dysmenorrhea have been less consistent when adenomyosis, or adenomyosis with leiomyomas, has been compared with those with pathology-confirmed leiomyomas. 12,43,[86][87][88][89][90][91][92][93] Although in several of these studies, patients with adenomyosis with or without leiomyomas appear to experience a greater frequency of dysmenorrhea than patients with leiomyomas. 12,86,87,90,92 One frequently cited study has suggested that adenomyosis is an incidental finding and not a source of symptoms.…”
Section: Symptomatologymentioning
confidence: 99%
“…The authors hypothesized that endomyometrial junction deterioration during endometrial sampling may be a trigger point for developing adenomyosis. 11 In another study also clinical and pathological correlation were poor, when DUB was the preoperative clinical diagnosis. Based on their observation here the authors suggested hysterectomy specimens should be sent for histopathology regardless of the preoperative histopathology of the endometrium.…”
Section: Discussionmentioning
confidence: 94%
“…Other researchers reported lower sensitivity, at 48 and 53% [70][71][72][73][74][75][76][77][78][79][80]. Other studies, with a larger number of women, are needed to address this issue [81][82][83][84][85].…”
Section: Diagnosismentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been applied to pelvic pathology and the initial results in women with adenomyosis are encouraging [75][76][77][78][79][80][81][82][83][84]. Mark and his colleagues predicted adenomyosis in eight of 20 women studied with T2 images.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation